Coral Record of Younger Dryas Chronozone Warmth on the Great Barrier Reef. Issue 12 (16th December 2020) - Brenner, Logan D.; Linsley, Braddock K.; Webster, Jody M.; Potts, Donald; Felis, Thomas; Gagan, Michael K.; Inoue, Mayuri; McGregor, Helen; Suzuki, Atsushi; Tudhope, Alexander; Esat, Tezer; Thomas, Alex; et al.
Abstract: The Great Barrier Reef (GBR) is an internationally recognized and widely studied ecosystem, yet little is known about its sea surface temperature (SST) evolution since the Last Glacial Maximum (LGM) (~20 kyr BP). Here, we present the first paleo‐application of Isopora coral‐derived SST calibrations to a suite of 25 previously published fossil Isopora from the central GBR spanning ~25–11 kyr BP. The resultant multicoral Sr/Ca‐ and δ 18 O‐derived SST anomaly (SSTA) histories are placed within the context of published relative sea level, reef sequence, and coralgal reef assemblage evolution. Our new calculations indicate SSTs were cooler on average by ~5–5.5°C at Noggin Pass (~17°S) and ~7–8°C at Hydrographer's Passage (~20°S) (Sr/Ca‐derived) during the LGM, in line with previous estimates (Felis et al.,   2014, https://doi.org/10.1038/ncomms5102 ). We focus on contextualizing the Younger Dryas Chronozone (YDC, ~12.9–11.7 kyr BP), whose Southern Hemisphere expression, in particular in Australia, is elusive and poorly constrained. Our record does not indicate cooling during the YDC with near‐modern temperatures reached during this interval on the GBR, supporting an asymmetric hemispheric presentation of this climate event. Building on a previous study (Felis et al.,  2014, https://doi.org10.1038/ncomms5102 ), these fossil Isopora SSTA data from the GBR provide new insights into the deglacial reef response, with near‐modern warming during the YDC, since the LGM. Key Points: Near‐modern sea surface temperatures were reached during the Younger Dryas Chronozone on the Great Barrier Reef Sea surface temperature, reef assemblage, and sea level data provide an overview of the evolution of the Great Barrier Reef since the LGM Isopora‐ based sea surface temperature calibrations can be applied to fossil Isopora to understand environmental change on coral reefs